The role of character education in learning during the COVID-19 pandemic - Enika Vera Intania; Sutama Sutama (Jurnal Penelitian Ilmu Pendidikan, 2020)
Abstract Coronavirus Disease-2019 (COVID-19) has an impact on all aspects of life, including education. Face-to-face education must be transferred to online learning. In learning, both face-to-face and online, character education must always be instilled in students. Character education is an important thing that students must have in order to grow their character, so they can have good personalities In a pandemic such as now, character education is very necessary for students to continue to develop their potential, even though learning is carried out online. The purposes of this study are 1) Analyzing the role of character education in learning; 2) Describing the role of character education in learning in the pandemic era of COVID-19. This type of research is a reference research. The object of this research is the role of character education in learning in the COVID-19 pandemic era. Data validity is done by Triangulation of Sources and Triangulation of Extension. In this study, data analysis techniques used constant comparison. The results of the study are twofold, 1) Character education in learning has a role for students to foster good character that can be realized in their social life; 2) In the pandemic era COVID-19 character education can play a role so that students independently want to learn material and develop an attitude of responsibility towards the tasks given by the teacher in online learning. Peran pendidikan karakter dalam pembelajaran selama pandemi COVID-19Pandemi COVID-19 menimbulkan dampak pada semua aspek kehidupan, termasuk pendidikan. Pendidikan tatap muka harus dialihkan ke pembelajaran online. Dalam belajar, baik tatap muka maupun online, pendidikan karakter harus selalu ditanamkan pada siswa. Pendidikan karakter merupakan hal penting yang harus dilakukan siswa agar dapat menumbuhkan karakternya, sehingga mereka dapat memiliki kepribadian yang baik Di masa pandemi seperti sekarang, pendidikan karakter sangat diperlukan bagi siswa untuk terus mengembangkan potensinya, meskipun pembelajaran dilakukan secara online. Tujuan penelitian ini adalah, 1) Menganalisa peran pendidikan karakter dalam pembelajaran; 2) Menggambarkan peran pendidikan karakter dalam pembelajaran di era pandemi COVID-19. Jenis penelitian ini adalah penelitian referensi. Objek penelitian ini adalah peran pendidikan karakter dalam pembelajaran di era pandemi COVID-19. Validitas data dilakukan dengan Triangulasi Sumber dan Triangulasi Ekstensi. Dalam penelitian ini, teknik analisis data menggunakan perbandingan konstan. Hasil penelitian menunjukkan bahwa 1) Pendidikan karakter dalam pembelajaran memiliki peran bagi siswa untuk menumbuhkan karakter baik yang dapat diwujudkan dalam kehidupan sosialnya; 2) Di era pandemic, pendidikan karakter COVID-19 dapat berperan penting sehingga siswa secara mandiri ingin belajar materi-materi dan mengembangkan sikap tanggung jawab terhadap tugas-tugas yang diberikan guru dalam pembelajaran daring.